Alteration in glucose homeostasis and persistence of the pancreatic clock in aged mPer2Luc mice - Novosadová, Zuzana; Polidarová, Lenka; Sládek, Martin; Sumová, Alena (Scientific reports, 2018)
The physiological function of the pancreas is controlled by the circadian clock. The aim of this study was to determine whether aging-induced changes in glucose homeostasis affect properties of the circadian clock in the pancreas and/or its sensitivity to disturbances in environmental lighting conditions. mPer2 Luc mice aged 24–26 months developed hyperinsulinemic hypoglycaemia, which was likely due to the Pclo -mediated insulin hyper-secretion and Slc2a2 -mediated glucose transport impairment in the pancreas, and due to the alterations in Pp1r3c -related glycogen storage and Sgk1 -related glucose transport in the liver. In the pancreatic tissue, aging affected clock gene expression only marginally, it upregulated Bmal1 and downregulated Clock expression. Whereas aging significantly impaired the circadian clock in lung explants, which were used as a control tissue, the properties of the pancreatic clock in vitro were not affected. The data suggest a non-circadian role of Bmal1 in changes of pancreatic function that occur during aging. Additionally, the pancreatic clock was more sensitive to exposure of animals to constant light conditions. These findings provide an explanation for the previously demonstrated relationship between disturbances in the circadian system and disordered glucose homeostasis, including diabetes mellitus type 2, in subjects exposed to long-term shift work.